Analytical investigation and experimental validation of anchorage zone to improve bursting force equation for post-tensioned concrete members. (May 2023) - Jain, Monika; Khapre, Rajendra
Abstract: The anchorage zone is a critical component of post-tensioned concrete members, and its effect on transverse tensile stress and bursting force is of utmost importance. In the study undertaken, analytical investigation and experimental validation of the anchorage zone has been carried out in order to improve the bursting force equation presented in IS 1343 for post-tensioned concrete members. To determine the relative contribution of anchorage ratio (k), pre-stressing force, and duct opening in the modeling of the plate on bursting tensile stress and bursting force, 3D Finite Element Analysis (FEA) was conducted. The results indicate that the equation recommended by IS 1343 underestimates the bursting force. To address this, an updated design equation is proposed in the same form as presented by IS 1343.